EVALUASI FUNGSI EKOSISTEM DI PERTAMBANGAN NIKEL KECAMATAN POMALAA SULAWESI TENGGARA - Erfina, Erfina (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
Mining activities have a negative impact on the environment. The ecosystem around the nickel extraction area of ​​Pomalaa District has been heavily polluted. disrupting the functions of the ecosystem. This study aims to assess the ecosystem function in the country of nickel mining in the Pomalaa district. The LFA results in the three regions have a terrestrial stability of 38.40 ± 1.3% (North Mine), 37.43 ± 1.3% (Central Mine) and 31.47 ± 0, 5% (south mine). The water infiltration index was 25.8 ± 2.3% (North T.), 24.63 ± 1.8% (Middle T.), 24.70 ± 0.5% (South Mine). ) and the nutrient cycle was 16.37 ± 3% (North Mine), 14.3 ± 0.5 (Central Mine), 13.83 ± 0.07 (South Mine). Low Complexity Index of 5 (North Mine), 4 (Central Mine) and 3 (South Mine) showing undeveloped habitat. It can be concluded that the ecosystem of the Kec nickel district. Pomalaa has experienced a disruption of regulatory functions, habitat and ecosystem biomass production is not well.